CRYSTAL STRUCTURE, HIRSHFELD SURFACE ANALYSIS AND ENERGY FRAMEWORK STUDY OF THE NITRONE N-BENZYLIDENE-N-BUTYLAMINO-4-Β-PYRIDYL-N-OXIDE - Delgado, Gerzon E; Mora, Asiloé J.; Bahsas, Ali; Koustnetzov, Vladimir V.; Chacón, Cecilia; Cisterna, Jonathan; Cardenas, Alejandro; Brito, Ivan (Journal of the Chilean Chemical Society, 2020)
The title compound, C16H16N2O, a potential antiparasitic agent, crystallizes in the orthorhombic Pca21 space group with unit cell parameters a= 9.912(1) Å, b= 9.035(1) Å, c= 15.681(2) Å. The crystalline structure is stabilized by weak C—H···O and C–H···Cg(π) interactions among neighboring molecules producing an efficient packing with 66.0% of occupied space. The C–H···O hydrogen bond keeps the molecules linked into supramolecular chains propagating along the a axis direction with a graph-set notation C(4), which are reinforced by C–H···Cg(π) interactions. Hirshfeld surface analysis of the intermolecular contacts reveal that the most important contributions for the crystal packing are from H··H (55.2%) and H··C/C··H (27.1%) interactions. Energy framework calculations suggest that the contacts formed between molecules are slightly dispersive in nature.